Determination of factors affecting the quality of life in children with asthma - Şancı Çekingen, Yağmur; Büyükgönenç, Lale Ayşegül (The European Research Journal, 2020)
Objectives: This study has been conducted in order to determine the factors affecting the quality of life in children with asthma. Methods: The study sample consisted of 103 children (aged 7-16). Data has been collected using socio-demographic questionnaire and Pediatric Asthma Quality of Life Questionnaire (PAQLQ) through face to face interviews. Results: Seventy-eight point six percent of the children’s daily activities were affected due to asthma. Evaluating the sub-groups mean scores of the life quality of the children; the highest mean score was in the symptoms group. The activity limitation sub-group mean score was significantly decreased with the increase of the number of people living in the house and other siblings having asthma too. The symptom sub-groups mean scores of the children that are exposed to smoke and psychological factors and which state that their daily activities are being affected was lower. The emotional function sub-groups mean score of the children that are exposed to psychological factors was significantly decreased. The scale total mean score of the children with sensitivity to cockroach and psychological factor stimulant was lower (p < 0.05). Conclusions: It’s been suggested that the stimulants which trigger the symptoms, asthma disease, accurate and effective medication treatment and self-care should be taught to the child and the family; home care continuity should be ensured and arranging the environment to reduce the child’s connection with the allergens that could trigger the asthma attack is necessary.